MEDIASI MOTIVASI KERJA PADA HUBUNGAN KOMPENSASI DAN GAYA KEPEMIMPINAN TERHADAP SEMANGAT KERJA - Khasanah, Masrikhatun; Fu’ad, Eko Nur (Jurnal Manajemen & Bisnis Jayakarta, 2024)
Abstract is written concisely and factually, includes the background of research, the purpose of research, the method of research, the result of research, conclusion, and recommendation. Abstract is written in one paragraph, font Times New Roman 11, italic and 1 spacing. This study aims to determine the effect of compensation and leadership style on employee morale with motivation as an intervening variable at CV. Jati Sarana Mulia. The data for this study were obtained from distributing questionnaires to 65 employees of CV. Jati Sarana Mulia. The sampling technique in this study is total sampling, where the total sample and population used in this study are the same in number. The data analysis method used in this study is the Structural Equation Modeling equation model using variance or component based structural equation modeling. After analyzing the data, the results of this study indicate that compensation has a positive and significant effect on employee morale. Motivation has a positive and significant effect on employee morale. Leadership style has no effect on employee morale. Compensation has a positive and significant effect on work motivation. Leadership style has a positive and significant effect on work motivation. Compensation has a positive and significant effect on morale through motivation. Leadership style has no effect on morale through motivation.